Association of polymorphism rs11656696 in GAS7 with primary open-Angle Glaucoma in a Chinese Population. (4th May 2019) - Xu, Jiaxin; Luo, Huanchao; Yu, Man; Yang, Chen; Shu, Yi; Gong, Bo; Lin, Yin; Wang, Jin
ABSTRACT: Background : It has been shown that genetic factors play an important role in the pathogenesis of primary open-angle glaucoma (POAG). This study was conducted to investigate the association between the polymorphism rs11656696 located in the growth arrest-specific 7 gene ( GAS7 ) and POAG. Methods : A cohort of 799 unrelated POAG patients and 799 unrelated control subjects was enrolled in this case-control association study. The polymorphism rs11656696 was genotyped using the SNaPshot method. The genotype and allele frequencies were evaluated using the χ 2 tests. Results : The allele frequency distribution of rs11656696 in the GAS7 gene showed that there was significant difference between POAG cases and controls ( P = .006448, OR = 0.82, 95%CI = (0.72–0.95). The minor "A" allele frequency of this polymorphism was 0.477 in the POAG cases, whereas it was 0.526 in controls, suggesting a protective effect for POAG. Significant associations were detected under the homozygous model ( p = .006425, OR = 0.68, 95%CI = 0.51–0.90) and recessive model ( p = .0003432, OR = 0.66, 95%CI = 0.52–0.84), indicating that subjects carrying rs11656696 AA genotype were less likely to suffer from POAG than those carrying AC/CC genotypes. Conclusion : This case-control association study showed that polymorphism rs11656696 in GAS7 is related to POAG and might be a protective factor against POAG.